Strategic choices and programme priorities for the ASARECA Animal Agriculture Research Network (A-AARNET). 2005-2015. Executive summary - Ndikumana, J. (International Livestock Research Institute, 2005)
This executive summary document like the main document is divided in eight parts. The first part is introduction, followed by sections two to eight, which comprise review of research domain; evaluation of past research; constraints and opportunities analysis; determination of sub-themes; policy recommendations; and conclusion.